POTENTIAL PLANTS BALIK ANGIN (Alphitonia excels (Fenzl) Benth.) AS ANTI TUMOR - samsul Hadi (Prodi Farmasi - Universitas Al Ghifari, 2022)
Cancer is a disease characterized by uncontrolled cell duplication and the ability of cells to invade other biological tissues. Thus treatment of this disease needs to be done. However, treatment of this disease poses a relatively high risk. So that research is needed to find compounds that have the potential to overcome cancer. By looking at the stability of the ligand interacting with the BCl2 receptor. One of the plants that has the potential as an alternative cancer treatment is Alphitonia excels and one of the methods that can be used to see stability is docking. This docking process begins with protein preparation with Yasara and ligand preparation with Marvinbean. Docking software used is PLANT and visualization of interactions with Discovery studio. The results of the docking score are Batulinic acid :-75,487; Alphitonin :-81,143; Alphitolic acid :-78,293; Ceanothic acid :-73,27. So it can be concluded that the most stable ligand interacting is Alphitonin.